THE RELATIONSHIP BETWEEN ADHERENCE TO IRON SUPPLEMENTATION AND THE INCIDENCE OF ANEMIA IN THIRD TRIMESTER PREGNANT WOMEN - Sefrina Rukmawati; Syahfilah Andara Early (Journal for Quality in Women's Health, 2026)
Anemia in pregnancy is a global health problem affecting approximately 41.8% of pregnant women worldwide. Iron supplementation is the main program for anemia prevention, but adherence remains low. The study used a cross-sectional design with consecutive sampling technique on 34 third trimester pregnant women at [location] Health Center. Data were collected using an iron supplementation adherence questionnaire and hemoglobin level examination. Data analysis used Chi-Square test with significance level p<0.05. The results showed that 62.5% of respondents were non-adherent to iron supplementation and 58.3% had anemia. There was a significant relationship between adherence to iron supplementation and the incidence of anemia (p=0.001; OR=4.523). Non-adherent pregnant women had 4.5 times greater risk of anemia compared to adherent ones. This study concludes that adherence to iron supplementation plays an important role in preventing anemia in third trimester pregnant women.